Lens coupler and magnetic field terahertz emission enhancement in InSb and InAs under 1.55-μm excitation - Nakajima, Hidekazu (Animo Repository, 2013)
Terahertz (THz) emission from InSb and InAs utilizing an MgO lens coupler in conjunction with an applied magnetic field is reported. A THz peak amplitude enhancement of 74 times in InSb compared to 26 times in InAs was observed. The considerable enhancement in InSb is attributed to its large Hall angle, small THz divergence and reduced total internal reflection. A corresponding emission shift to lower THz frequencies in both samples was observed due to the spectral dependence of the MgO lens' collection efficiency. This enhancement configuration is easily applicable in the design of a compact THz time-domain spectroscopy system. © 2013 The Japan Society of Applied Physics.